10 Years of TROLLing: A Birthday Podcast Episode - Janda, Laura A.; Sönning, Lukas; Aspaas, Per Pippin (Open Science Talk, 2024)
The Tromsø Repository of Language and Linguistics (TROLLing) published its first dataset on June 13, 2014. Since then, the repository has grown to 173 datasets, each of which is available in open access and equipped with metadata explaining its contents. Two of the most frequent users of the archive, professor of Russian linguistics Laura A. Janda and postdoc of English linguistics Lukas Sönning share their experiences and ideas for the future. A key message is how using a curated data repository has helped raising the quality of their own research by making it more transparent and reusable for others. Materials referred to in the episode include: a humorous YouTube clip (2014) featuring Laura A. Janda and others; a Leiden dissertation (later published as a book) by Jaap Kamphuis; a workshop at the ISLE 5 conference (2018) organised by Lukas Sönning and Valentin Werner; a paper at the ICAME 45 conference (2024) by Lukas Sönning, Jason Grafmiller and Raquel P. Romasanta. First published online: June 12, 2024.